Revenge of Odessa - Forsyth, Frederick, 1938-2025; Kent, Tony (Crime fiction writer) (G. P. Putnam's Sons, 2025)
"Fifty years after revealing the secrets of Odessa, an underground organization of former Nazis angling to regain power, Peter Miller is a retired legend in the journalism community. He's spent the last decade caring for his grandson Georg after the death of his son and daughter-in-law in a tragic car accident. Always suspecting that his own long list of enemies might have been behind his son's death, Peter pulled back from his career to keep Georg safe. But he could do nothing to stop the young man from following in his footsteps--Georg's reputation and renown for fearless journalism growing fast in a digital world. But Georg Miller is not the only aspect of Peter's past that has thrived"--